Thailand's National Nutritional Program : Lessons in Management and Capacity Development - Heaver, Richard (World Bank, Washington, DC, 2013)
Thailand's community nutrition program has been the most successful in Asia. This paper looks at what made it work from a management and capacity development point of view. Key lessons are identified in the following areas: Building a strong consensus at national and local levels about the importance of nutrition as an investment in the country's future, rather than as a welfare expenditure; using community volunteers on a huge scale, to cut costs, involve and empower local people, instill self-reliance and communicate effectively with target groups; partially empowering communities by involving them in needs assessment, planning, beneficiary selection and program implementation, but keeping central government control over resource allocation, so as to ensure a coherent national program; Seeking local financial contributions to almost all interventions, so as to cut costs, involve communities, instill self-reliance, and increase the chances of sustainability; Making the most use of limited financial and managerial resources by targeting needy provinces, sub-districts and villages, and high risk population groups; Using national nutrition investment plans, rather than policy statements unlinked to resource commitments, as a way of generating a national vision, giving visibility to nutrition, and giving each implementing agency clear responsibilities; Managing the nutrition sector through a series of committees, rather than by a single agency, which encouraged a wide variety of interest groups to feel that nutrition was their business; Building a strong nutrition technical support organization, which also helped maintain commitment to nutrition; Using small amounts of aid for training and building program support capacity, rather than funding large scale service delivery projects. Also discussed is whether the approaches used in Thailand are replicable in other countries, and what nutrition problems and issues remain to be addressed in Thailand.